2022
DOI: 10.3390/batteries8040033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Switching on the Aging of High Power Lithium-Ion Cells

Abstract: For intelligent battery systems that are able to control the current flow for each individual cell, the multilevel inverter is an interesting approach to replace the bidirectional AC/DC-converter and improve flexibility of charging system and signal quality in both directions. Therefore, the cells are modulated by switching varying the duty cycle, the current and the frequency up to the kHz-range. This is only beneficial if the switching does not lead to a significant additional aging. The scientific gap to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…No increased aging was observed here, but the pulsed charging might have a positive effect on the resistance of the solid-electrolyte interphase. In summary, the authors of [27] concluded that the aging of high-power cells is not significantly affected by switching operations.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…No increased aging was observed here, but the pulsed charging might have a positive effect on the resistance of the solid-electrolyte interphase. In summary, the authors of [27] concluded that the aging of high-power cells is not significantly affected by switching operations.…”
Section: Resultsmentioning
confidence: 97%
“…To reduce the current RMS, switching strategies can be applied to limit switching to periods with low currents or low excitation in a frequency domain, e.g., using the Goertzel algorithm [13,25]. Furthermore, in the work of Ngaleu et al [27], the influence of switching at 50 Hz and 10 kHz on aging was investigated using the same cell type as in this paper. No increased aging was observed here, but the pulsed charging might have a positive effect on the resistance of the solid-electrolyte interphase.…”
Section: Resultsmentioning
confidence: 99%